Efektifitas Pemberian Dana Tunjangan Profesi Guru dalam Peningkatan Kompetensi Guru Sekolah Menengah Pertama - Irwan Rifai; Warjio Warjio; Maksum Syahri Lubis (Mahesa Research Center, 2022)
This study aims to determine the effectiveness of providing teacher professional allowances in improving teacher competence at SMP Negeri 1 Rantau Selatan Labuhanbatu Regency in 2019. This type of research is a qualitative descriptive study. . And then, for the sample used with the key person method as many as 14 people, namely principals and teachers who have been certified. The technique of collecting data uses the method of observation, interviews and documentation, while the data analysis technique used is the data analysis method, which is called data triangulation according to Miles and Huberman. The results of this study indicate that: (1) The provision of Teacher Professional Allowance (TPA) funds at SMP Negeri 1 Rantau Selatan has been effective and the provision of TPA funds for teachers is used as best as possible to be used to improve teacher quality so that they are more competent both in the pedagogical and professional fields ; and (2) the factors that influence the provision of the Teacher Professional Allowance to increase teacher pedagogical and professional competence, namely because the government wants to help the welfare of teachers in order to improve teacher competence both in pedagogic and professional in accordance with the development of science and technology.